2010
DOI: 10.1080/13632460903294390
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Double Variable Frequency Pendulum Isolator under Triaxial Ground Excitations

Abstract: Modeling techniques of double variable frequency pendulum isolator (DVFPI) are presented. Seismic responses of the three-dimensional single-story building isolated by DVFPI with different coefficient of friction and initial time period of top and bottom sliding surfaces are investigated under triaxial ground motions and compared with unilateral and bilateral ground excitations. Furthermore, the influence of vertical flexibility on horizontal response is also investigated. It is observed that the triaxial groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Besides concave sliding surface designs, Lu et al [15] and Saha et al [16] analytically and experimentally studied some complicated polynomial functions designed for the sliding surfaces of FPBs so as to present variable stiffness properties and thus achieve multiple design objectives. Furthermore, in addition to studying the unilateral behavior of double or triple FPBs, their multi-axial behavior was thoroughly studied by Panchal et al [17], Becker and Mahin [18], Sah and Soni [19], and Furinghetti et al [20]. Some research results indicated that the effect arising from vertical excitations on the horizontal seismic performance of double or triple FPBs might not be negligible for obtaining more accurate and conservative design results [21,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides concave sliding surface designs, Lu et al [15] and Saha et al [16] analytically and experimentally studied some complicated polynomial functions designed for the sliding surfaces of FPBs so as to present variable stiffness properties and thus achieve multiple design objectives. Furthermore, in addition to studying the unilateral behavior of double or triple FPBs, their multi-axial behavior was thoroughly studied by Panchal et al [17], Becker and Mahin [18], Sah and Soni [19], and Furinghetti et al [20]. Some research results indicated that the effect arising from vertical excitations on the horizontal seismic performance of double or triple FPBs might not be negligible for obtaining more accurate and conservative design results [21,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A new material, shape memory alloy (SMA), has been utilized in the rubber bearings to limit the displacement and provide the energy dissipation [23][24][25][26][27], but less investigation has been carried out on the VFPI. Additionally, due to the complex of the sliding geometry of the VFPI, the contact between the slider and surface may result in tear and local damage due to stress concentration [28]. The design compressive stress of the commonly used polytetrafluoroethylene (PTFE) plate is only 30 Mpa [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, analytical studies have reported an increase of several response parameters of structures isolated with friction bearings subjected to 3D excitation in comparison with 2D. 20,21 The strong coupling evidence in the TPB configuration was shown to result from the friction mechanism in the bearings. 22 However, the H-V coupling observed in the LRB/CLB and fixed-base configurations has not yet been fully explained.…”
mentioning
confidence: 99%